INFLUENCE OF LEAD ON GROWTH AND PHYSIOLOGICAL CHARACTERISTICS OF A FRESHWATER GREEN ALGA CHLORELLA SP. - Teoh, Ming-Li; Wong, Siu-Wan (Malaysian Journal of Science, 2018)
Pollution caused by heavy metals poses a serious challenge to ecosystems. Microalgae are microscopic algae that form the base of the food chain in aquatic ecosystems. Heavy metals present in soils can leach into aquatic ecosystems, leading to bioaccumulation by organisms through the food chain, and exerting toxic effects on microalgae, the primary producers. This study reports the response of the alga Chlorella sp. to lead stress over experimental exposures of 11 days. Chlorella sp. were grown and exposed to different lead concentrations (0, 10, 25, 50, 75 and 100 mg/L) at 18ÂºC. The experiments were conducted in triplicate. Growth rate of microalgae was determined by measuring the optical density at 620 nm (OD620) and chl-a concentration. The data obtained showed that lead affects the physiological characteristics (growth, chl-a and carotenoids) and protein content of Chlorella sp. Exposure to increasing lead concentrations resulted in decreasing specific growth rate (Âµ), chlorophyll-a, carotenoid and protein contents. However, the data obtained indicate that Chlorella sp. can tolerate the toxicity of lead even at high concentration. Keywords: Chlorella, heavy metals, lead, specific growth rate, protein